Smart Travel Alarm – An Android app on Sencha2.2 (International Journal of Engineering and Computer Science, 2014)
In this modern world Smartphones and Tablets are need for every group from Children, teens, Parents, Business executives, Professionals to old age people. With this techy gadgets, location based applications are widely used as it makes life very easier, faster and keeps track of our near and dear ones as well as our business associates. The SMART Travel Alarm is designed to provide high tech services to users based on the information of their current geographic locations. Some of these services include “Reached to destination alarm”, Email someone on reaching the destination etc. In this paper we illustrates the development of SMART Travel Alarm - a Android application based on Sencha 2.2 framework using Google Web Services to offer multiple services to the users on the move. The developed app works perfectly fine on major smartphones and tablets running on various versions of android OS.